2018
DOI: 10.1016/j.euromechsol.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A new four-dimensional ratcheting boundary: Derivation and numerical validation

Abstract: A new four-dimensional ratcheting boundary is derived analytically for the first time considering the interaction among four types of stresses: constant mechanical membrane stress, mechanical bending stress, cyclic thermal membrane stress, and thermal bending stress. A uniaxial beam model is used to derive the closed-form ratcheting boundary for these combined cyclic and constant loadings.The Tresca yield condition and elastic-perfectly plastic behavior are assumed. A novel two-plane FE model is proposed for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…(11)(12)(13)(14)(15)(16) and the effective creep stress parameters given by Eqs. (18)(19)(20)(21)(22), the above theoretical solutions and numerical solutions based on the finite element step-by-step analysis are compared. The common two-plane model proposed by the authors [22] for uniaxial Bree-type problems is adopted for numerical analysis, as shown in Fig.…”
Section: Elastic Core Concept Of Modified Bree Problem Considering In...mentioning
confidence: 99%
See 1 more Smart Citation
“…(11)(12)(13)(14)(15)(16) and the effective creep stress parameters given by Eqs. (18)(19)(20)(21)(22), the above theoretical solutions and numerical solutions based on the finite element step-by-step analysis are compared. The common two-plane model proposed by the authors [22] for uniaxial Bree-type problems is adopted for numerical analysis, as shown in Fig.…”
Section: Elastic Core Concept Of Modified Bree Problem Considering In...mentioning
confidence: 99%
“…The mismatch between the simplified assessment method and the actual situation will lead to conservative or non-conservative problems. Currently, some progress has been made in the modified Bree problems considering the effects of multiple stress parameters, such as the work of Reinhardt [18], Adibi-Asl [19], Shen [20], Bao [21,22], etc. The development of a multi-dimensional effective creep stress parameter diagram is worthy of further study.…”
Section: Introductionmentioning
confidence: 99%
“…Ratcheting is an accumulated inelastic deformation or strain. Ratcheting may occur when a component subjected to cyclic mechanical stress, thermal stress, or their combination [3]. When cyclic thermal stress existed, thermal stress ratcheting may happen.…”
Section: The Outline Of a Pche And Bonded Sectionmentioning
confidence: 99%
“…where, α i can be calculated from the monotonic test and upper hysteresis curves by Equations (10) and (11), respectively.…”
Section: Chaboche Model Of Ratchetingmentioning
confidence: 99%
“…Offshore structures, pressure vessels and piping system, structures operating in earthquake zones, airplane landing gears and nuclear reactors are typical examples of such components and structures [6][7][8]. Structures subjected to stress cycles beyond the elastic limit oblige a trustworthy design, especially in the presence of a significant mean stress from loads such as dead weight or internal pressure [1,6,9,10].…”
Section: Introductionmentioning
confidence: 99%